The acute management of haemorrhage, surgery and overdose in patients receiving dabigatran. Issue 2 (22nd February 2013) - Alikhan, Raza; Rayment, Rachel; Keeling, David; Baglin, Trevor; Benson, Gary; Green, Laura; Marshall, Scott; Patel, Raj; Pavord, Sue; Rose, Peter; Tait, Campbell
Abstract : Dabigatran is an oral direct thrombin inhibitor (DTI) licensed for stroke prevention in atrial fibrillation and likely to be soon approved in Europe for treatment of venous thrombosis. Predictable pharmacokinetics and a reduced risk of intracranial haemorrhage do not negate the potential risk of haemorrhage. Unlike warfarin, there is no reversal agent and measurement of the anticoagulant effect is not 'routine'. The prothrombin time/international normalised ratio response to dabigatran is inconsistent and should not be measured when assessing a patient who is bleeding or needs emergency surgery. The activated partial thromboplastin time (APTT) provides a qualitative measurement of the anticoagulant effect of dabigatran. Knowledge of the time of last dose is important for interpretation of the APTT. Commercially available DTI assays provide a quantitative measurement of active dabigatran concentration in the plasma. If a patient receiving dabigatran presents with bleeding: omit/delay next dose of dabigatran; measure APTT and thrombin time (consider DTI assay if available); administer activated charcoal, with sorbitol, if within 2 h of dabigatran ingestion; give tranexamic acid (1 g intravenously if significant bleeding); maintain renal perfusion and urine output to aid dabigatran excretion. Dabigatran exhibits low protein binding and may be removed by dialysis. Supportive care should form the mainstay of treatment. If bleeding is life/limb threatening, consider an additional haemostatic agent. There is currently no evidence to support the choice of one haemostatic agent (FEIBA, recombinant factor VIIa, prothrombin complex concentrates) over another. Choice will depend on access to and experience with available haemostatic agent(s).